Application of seismic refraction tomography for tunnel design in santa clara mountain, san juan, argentina (2011)
A geophysical survey involving seismic refraction tomography (SRT) for mapping 'P' waves was carried out in Sierra Santa Clara, San Juan Province, Argentina in July 2009. The purpose of the geophysical survey was to determine the degree of fracturing and the rigidity of the rock mass through which it is planned to build a 290 m long road tunnel traversing the mountain almost perpendicular to the axis thereof, at around 100 m depth from the summit. Several difficulties arose from the operational point of view which made it almost impossible to conduct fieldwork in normal circumstances. Firstly, the topography had almost 45º slopes and 100 m research depths which would have involved having had to use explosives to generate seismic waves reaching sensors which had sufficient signal-to-noise ratio for distinguishing them. Legal restrictions regarding the use of explosives on the one hand and insufficient power when using  hammer blows on the other made it necessary to design and build a gas-powered gun to achieve the minimum energy (2 kJ) required for detecting seismic signals. Secondly, using conventional interpretation methods involving layered models was inoperable in such geological structures; seismic tomography methods were thus used which make use of the velocity gradient concept (both lateral and in-depth). This allowed mapping subsurface velocity variations in the form of velocity contour lines.  The methodology used with the new seismic waves' source generator, as well as SRT application in this type of geological structure, demonstrated that satisfactory results could be obtained for this kind of geophysical study for geotechnical purposes.